Biology Teachers'Conceptions of the Diversity of Life and the Historical Development of Evolutionary Concepts - Silva, Paloma Rodrigues da [UNESP]; Bologna Soares de Andrade, Mariana A.; Andrade Caldeira, Ana Maria de [UNESP] (Routledge Journals, Taylor &francis Ltd, 2015)
Biology is a science that involves study of the diversity of living organisms. This diversity has always generated questions and has motivated cultures to seek plausible explanations for the differences and similarities between types of organisms. In biology teaching, these issues are addressed by adopting an evolutionary approach. The aim of this study was to compare the extent to which the beliefs of 20 public high school biology teachers in the Bauru region of Sao Paulo in Brazil exemplified the most significant historical concepts regarding evolution. Data from open-ended interviews with teachers were analysed and coded. The analysis of the interviews revealed how participating biology teachers understood and explained biological evolution. The assessment of teachers'conceptions about evolution indicated that many responses expressed current scientifically accepted concepts, such as transformism, natural selection, gradualism and common descent. However, some teachers also provided responses that combined scientific concepts with non-scientific notions, such as finalism, verticality and adaptation to the environment. Therefore, it is necessary to thoroughly investigate biology teachers'understanding of evolutionary processes.
Keywords: Conceptions of teachers; Teaching of biology; Biological evolution